Redevelopment of central jail area: Lalbagh, old Dhaka - Mymuna, Sk. Suraiya (BRAC University, 2012)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture in Architecture, 2012.